Recent Advances in Polysaccharide-Based Electrospun Nanofibers for Food Safety Detection - Jie Shi; Junjie Tang; Mengfei Zhang; Yingqi Zou; Jie Pang; Chunhua Wu (Sensors)
The continuous advancement of food safety analytical technologies is ensuring food safety and regulatory compliance. Electrospinning, a versatile fabrication platform, has emerged as a transformative methodology in materials science due to its unique capacity to generate nanoscale fibrous architectures with tunable morphologies. When combined with the inherent biodegradability and biocompatibility of polysaccharides, electrospun polysaccharide nanofibers are positioning themselves as crucial components in innovative applications in the fields of food science. This review systematically elucidates the fundamental principles and operational parameters governing electrospinning processes, with particular emphasis on polysaccharide-specific fiber formation mechanisms. Furthermore, it provides a critical analysis of state-of-the-art applications involving representative polysaccharide nanofibers (e.g., starch, chitosan, cellulose, sodium alginate, and others) in food safety detection, highlighting their innovative application in livestock (chicken, pork, beef), aquatic (yellow croaker, Penaeus vannamei, Plectorhynchus cinctus), fruit and vegetable (olive, peanut, coffee), and dairy (milk) products. The synthesis of current findings not only validates the unique advantages of polysaccharide nanofibers but also establishes new paradigms for advancing rapid, sustainable, and intelligent food safety technologies. This work further proposes a roadmap for translating laboratory innovations into industrial-scale applications while addressing existing technological bottlenecks.